The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1590/1981-863720200001820200088
|View full text |Cite
|
Sign up to set email alerts
|

Individual biosafety barrier in dentistry: an alternative in times of covid-19. Preliminary study

Abstract: ABSTRACT The return to dental practice in pandemic times is a new challenge due to the generation and dispersion of droplets and aerosols that may contain the SARS-CoV-2 virus, the etiological agent of covid-19. In the last months some droplet and aerosol containment strategies have been circulating on the internet, however, until now there is no evidence in the literature to prove the effectiveness of such barriers. Thus, using a microbial dispersion model with the fast handpiece, the aim of this prel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 17 publications
(28 reference statements)
0
15
0
4
Order By: Relevance
“…Although the methodology used was established with only one bacterial species ( Lactobacillus casei Shirota), its main objective was to use a viable biological marker in the water reservoir of the dental chair, and consequently, provide a simulation of PCDP in dental procedures. This proposed model has already been used in a previous study and has shown no significant environmental risks [ 8 ], which is extremely important in this pandemic period. In addition, an enriched culture medium was used for the growth of Lactobacillus , thus providing more reliable results on PCDP generated during the experiments than germ-free models.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the methodology used was established with only one bacterial species ( Lactobacillus casei Shirota), its main objective was to use a viable biological marker in the water reservoir of the dental chair, and consequently, provide a simulation of PCDP in dental procedures. This proposed model has already been used in a previous study and has shown no significant environmental risks [ 8 ], which is extremely important in this pandemic period. In addition, an enriched culture medium was used for the growth of Lactobacillus , thus providing more reliable results on PCDP generated during the experiments than germ-free models.…”
Section: Discussionmentioning
confidence: 99%
“…This strain was chosen because it is a bacterial species that poses no risk of environmental contamination and measures 0.5 μm (the SARS-CoV-2 virus measures 0.1 μm). Additionally, this microorganism has already been tested and validated for the dispersion model in a dental clinic environment in a previous study [ 8 ]. Thus, a viability test was performed to determine the initial concentration of 1.5x10 8 CFU / mL of L .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This strain was chosen because it is a bacterial species that poses no risk of environmental contamination and measures 0.5 μm (the SARS-CoV-2 virus measures 0.1 μm). Additionally, this microorganism has already been tested and validated for the dispersion model in a dental clinic environment in previous studies [ 2 , 11 ]. Thus, a viability test was performed to determine the initial concentration of 1.5x10 8 CFU / mL of L .…”
Section: Methodsmentioning
confidence: 99%
“…It is of considerable interest to have methods to reduce the dispersion of splashes/droplets/aerosols during procedures. In a preliminary study, the Individual Biosafety Barrier in Dentistry (IBBD), which is a biosafety device, was tested aiming to reduce the dispersion of droplets and aerosols generated during the service, reducing the CFU count by 95% [ 11 ]. Other studies have also used bacteria colony counts [ 3 , 12 ] and other fluorescent tracers to show the distribution of the ejected material in general [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%